2022
DOI: 10.1002/jdd.12901
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of learning outcomes of first year dental students using an interactive Nearpod educational platform

Abstract: The impact of COVID-19 required revisions in curricula, especially among professional programs that have traditionally required hands-on learning of content. This study endeavored to assess the level of effectiveness of the online presentation of material both qualitatively and quantitatively in a 5-week module on cariology for first-year dental students. Quantitative analysis of the assessment data was required to determine if an interactive engagement platform increased student outcomes. Quantitative survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…In relation to previous studies, the results of this study are consistent with previous reports, such as the one carried out by Ahmad & Siddiqui [24], where they made a comparison between the platforms Google Meet, Microsoft Teams, and Zoom and found that Zoom is the best platform for online learning. Another study that supports the data described in this article is the one carried out by Messina et al [25], where it was found that the ZOOM platform has benefits for carrying out evaluation activities with students. Finally, the study by Li et al [26] found that the ZOOM platform enables a successful transition from face-to-face to virtual education.…”
Section: -Discussionsupporting
confidence: 84%
“…In relation to previous studies, the results of this study are consistent with previous reports, such as the one carried out by Ahmad & Siddiqui [24], where they made a comparison between the platforms Google Meet, Microsoft Teams, and Zoom and found that Zoom is the best platform for online learning. Another study that supports the data described in this article is the one carried out by Messina et al [25], where it was found that the ZOOM platform has benefits for carrying out evaluation activities with students. Finally, the study by Li et al [26] found that the ZOOM platform enables a successful transition from face-to-face to virtual education.…”
Section: -Discussionsupporting
confidence: 84%
“…We categorised the included articles against the SAMR model in terms of the way learning technology was used in the educational process (see Appendices S1 and S2 for details). Various types of learning technologies were represented including technologies created specifically to support learning such as bespoke elearning modules, [21][22][23][24] virtual patients, 25-28 assessments [29][30][31][32][33][34][35][36][37][38][39][40] and mobile apps for learning. [41][42][43][44][45][46][47][48][49] Other technologies have been repurposed as learning technologies such as social media, 50,51 medical technologies-including digital microscopy, phonocardiography and digital X-rays, [52][53][54][55][56][57][58][59][60][61] and virtual and augmented reality.…”
Section: Samr Categorisationmentioning
confidence: 99%
“…[9] learning can be a challenge" [10] pedagogical design" [6] Table 3 "Qualitatively, the dental students overwhelmingly expressed support for the ease of use and educational value of the Nearpod platform." [16] "There were differences in pupils' relationship to digital technologies and in level of collaboration between the classes." [17] "Through the research, we found that Nearpod provides various perspectives that bring students into Global Warming."…”
Section: Resultsmentioning
confidence: 99%